Flavonoides de zornia brasiliensis e atividade antinociceptiva da 7-metoxiflavona - Silva, Anne Dayse Soares da (2013)
The genus Zornia has about 75 species worldwide, with 41 representatives in America, 16 in Africa, 13 in Asia-Oceania and 7 (MOHLENDROCK 1961), is the second most numerous representative of clade Adesmia. Occurs in Brazil from the Amazon region to the "pampas" in Rio Grande do Sul Zornia brasiliensis species is popularly known as "urinaria", "urinana" and "carrapicho" is reported by its use in folk medicine as a diuretic. It occurs in several states in Brazil, being abundant in northeastern Brazil occurring in the states of Alagoas, Bahia, Ceará, Pernambuco, Rio Grande do Norte and Paraiba. Here we describe the isolation and structural elucidation of flavonoids, chalcones and Pterocarpans aerial parts of Zornia brasiliensis. For this the plant material after drying and pulverization was subjected to extraction processes, partition and chromatography for isolation of the chemical constituents. The same chemical structure was determined by spectroscopic methods IR, Mass Spectrometry and Nuclear Magnetic Resonance 1H and 13C and uni-dimensional as well as comparisons with literature. Phases of dichloromethane and ethyl acetate afforded three of five compounds flavones: 7-methoxyflavone, 5-hydroxy-7-methoxyflavone and 5,7-dimethoxyflavone, a chalcone 2 ', 4'-dihidroxichalcona pterocarpan and a 3 - hydroxy-9-metoxipterocarpano, all isolated for the first time in the genre. Furthermore, this study evaluated the antinociceptive activity of 7-methoxyflavone isolated in this study. Thus, the results contributed to the expansion of knowledge of gender Zornia chemotaxonomic and antinociceptive activity of a flavone, so far not.